Research of the domestic market of drugs for the treatment of HIV infection - T. P. Zarichna; T. S. Brytanova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the research is to study the domestic market of medicines for the treatment of HIV infection to optimize the drug supply of the target group of patients.